Internalisasi Nilai-Nilai Moderasi Beragama Dalam Kegiatan Intrakurikuler di MA Negeri 1 (Model) Lubuklinggau - Rendi Kurniawan; Leny Marlina; Baldi Anggara (Jurnal Ilmiah Wahana Pendidikan, 2023)
The diversity that exists in our beloved homeland was a small part of His creation, in order to know and learn from each other so as to create a better, peaceful and peaceful treasure of civilization. School was like a miniature of society and the right place to build a moderate attitude through internalization in intracurricular activities. This research aims to find out how the process of internalizing religious moderation values ​​were carried out by teachers in intra-curricular activities at MA Negeri 1 (Model) Lubuklinggau. The research was used a qualitative approach and descriptive type of field research. In determining the informants, the researcher used a purposive sampling technique. As for collecting research data using observation, interview and documentation techniques, which will then be analyzed by means of data reduction, data presentation and data verification, then tested for validity using triangulation techniques. The results of the research show that the process of internalizing the values ​​of moderation in religion at MA Negeri 1 (Model) Lubuklinggau was carried out in three phases namely; firstly, through Madrasah Students Ta'aruf Period (MATSAMA), secondly through intracurricular activities, and thirdly through activities with nationalism and religious aspects such as group gymnastics, syarhil qur'an, cult every morning, tahfidz and art performances. As for the supporting and inhibiting factors, there were three, namely, student characteristics, teacher characteristics and the Madrasah environment.